Electrical Conductivity of Oxadiazole and Triazole Polymer Content - Asaad Khattab; Aya Wahhab (College of Education for Pure Sciences, 2021)
Three types of oxadiazle and traizole monomers were prepared. The monomers are polymerized with different monomers to prepare eight different polymers. The polymers are differs in the type of bonding unit. The prepared polymers are identified by using infrared spectroscopy and elemental analysis. The prepared polymers are doped with different ratios of iodine and protonic acid (HCl). The electrical conductivity of the pure and doped polymers was measured. Many different factors can effect on the conductivity of the polymers. The long flexible aliphatic moiety in the back bone of the polymer increase the electrical conductivity, while the presence of long aliphatic arm grafted as aside chain will decrease the conductivity. Also the type of the bonding group (amide or azomethin ) have a significant effect on the electrical conductivity. The study proved that the oxadiazole and triazole rings can participating in the conjugation of polymeric chain and enhanced the electrical conductivity. The nitrogen and oxygen atoms within the ring can participate with conjugation by their lone pair of electron and can be considered as a sites for doping. The electrical conductivity of the prepared polymers increased by increasing the ratio of the dopant but to limited percent. It was proved that the nitrogen atoms is more ready to protonated by acid than the oxygen atom